Comparison of the diagnostic value of serum pancreatic isoamylase and immunoreactive trypsin measurement in patients with cystic fibrosis. Issue 5 (May 1982) - Brown, R C; Chalmers, D M; Rowe, V L; Kelleher, J; Littlewood, J M; Losowsky, M S
Abstract : We have measured serum immunoreactive trypsin (IRT) and serum pancreatic isoamylase (PIA) activities using commercially available kits in 37 cystic fibrosis (CF) patients and 46 hospital controls of similar age range. Immunoreactive trypsin was more often abnormal than PIA (26/37 v 18/37 abnormal respectively); IRT will be particularly useful as an additional diagnostic test in older children, in whom interpretation of the sweat test may be difficult, as 14/15 CF patients aged over 10 years had abnormal IRT results. Less than half of our patients who were aged between one and nine years had abnormal IRT activity, limiting the value of the test, though a low activity would still support the diagnosis of CF. Comparison with faecal fat estimations in 31 patients suggests that neither IRT nor PIA can be used as a non-invasive test of pancreatic function in order to identify those few CF patients who do not require pancreatic enzyme supplements.